Pengaruh Profitabilitas Dan Mekanisme GCG Terhadap Nilai Perusahaan Dengan Pengungkapan CSR Sebagai Variabel Intervening - Chairunisa Apriliani; Gusmiarni Gusmiarni; Nuzulul Hidayati (Politeknik Ganesha Medan, 2023)
This research aims to examine the effect of profitability, intuitional ownership, audit committee and independent commissioners. This study uses firm value as the dependent variable and profitability, institutional ownership, audit committee and independent commissioners as independent variables, also corporate social responsibility (CSR) disclosure as an intervening variable. The sample used in this research was obtained by purposive sampling method. Based on existing criteria, during the period 2016 - 2020 obtained 15 companies that were sampled in this study. Of the 15 companies that met the sample criteria for a total period of five years, we obtained a total of 75 data. Using the help of the EViews 10.0 program, data analysis techniques began with a descriptive statistical test, continued with the classic assumption test, logistic regression analysis, analysis multiple linear regression panel data and the last was analysis of intervening variables. The results of this research indicate that the profitability and institutional ownership have a negative and not significant effect on corporate social responsibility (CSR) disclosure, while the audit committee and independent commissioners directly has a positive and not significant effect on corporate social responsibility (CSR) disclosure. Profitability directly has a positive and insignificant effect on firm value, while institutional ownership, audit committee and corporate social responsibility (CSR) disclosure directly have a negative and significant effect on firm value and independent commissioners directly has a positive and not significant effect on firm value. Profitability, institutional ownership, and independent commissioners indirectly through corporate social responsibility (CSR) disclosure does have a significant effect on firm value, while the audit committee indirectly through corporate social responsibility (CSR) disclosure does not have a significant effect on firm value. Profitability, institutional ownership, audit committee, independent commissioners, and corporate social responsibility (CSR) disclosure can explain 94.3% of the tax aggressiveness and the remaining 6.7% are explained by other variables not examined in this research.